Determining the size of the problem: a validation study to improve the assessment of mid-line breast cancer related lymphoedema - Riches, Katherine (2020)
Background: Lymphoedema can develop after treatment for breast cancer due to damage caused to the lymphatic drainage affecting the arm, breast and or chest wall. Most of the research on this topic has focused on the incidence and outcomes of breast cancer related lymphoedema (BCRL) of the arm. Despite the significant amount of research in this area, there is still much debate over the diagnostic criteria and the assessment techniques used.